2021
DOI: 10.3390/en14123452
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Energy and Environmental Assessment of the Thermal Insulation Improvement in Residential Buildings

Abstract: The refurbishment of the building stock is a key strategy towards the achievement of the climate and energy goals of the European Union. This study aims at evaluating the energy and environmental impacts associated with retrofitting a residential apartment to improve its vertical envelope thermal insulation. Two insulation materials, stone wool and cellulose fibers, are compared. The life cycle assessment methodology is applied assuming 1 m2 of retrofitted vertical envelope as functional unit. Moreover, to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Passive renovation minimizes heat transfer and, thus, energy use through wall insulation and roof coverings. Additionally, insulating the building envelope can mitigate structural damage risks from moisture, reduce material waste, and extend building lifespan, as shown by Cusenza et al [56]. Meanwhile, integrating PV systems into a building not only generates clean energy and reduces electricity usage but also enhances property value and elevates architectural appeal, as demonstrated by Polo López et al [57].…”
Section: Discussionmentioning
confidence: 99%
“…Passive renovation minimizes heat transfer and, thus, energy use through wall insulation and roof coverings. Additionally, insulating the building envelope can mitigate structural damage risks from moisture, reduce material waste, and extend building lifespan, as shown by Cusenza et al [56]. Meanwhile, integrating PV systems into a building not only generates clean energy and reduces electricity usage but also enhances property value and elevates architectural appeal, as demonstrated by Polo López et al [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, since this material has fire class D, some strategies should be adopted to improve the fire resistance of the whole construction. Most of the alternatives to overcome this hindrance are related to adding chemicals into the insulation material, such as boric acid (Veitmans & Grinfelds, 2016), contradicting the idea of the circular analysis, bringing harmful consequences into the environment, and carrying high collateral EE (An & Xue, 2014;Cusenza et al, 2021). As a potential alternative, using fire-resistant boards (such as fibre cement) on the outsides of the insulation material was the chosen solution for this research.…”
Section: Façade Designmentioning
confidence: 99%
“…It was concluded that when the thickness of foam concrete was 145 mm, the cold-proof effect was close to that of 50 mm thick polystyrene board exterior wall insulation. Cusenza et al (2021) used the life cycle assessment method to compare the effects of two thermal insulation materials, asbestos and cellulose fiber, on residential buildings in Europe. The results show that the use of cellulose fibers can reduce the impact of climate change (GWP) up to 20% and the consumption of primary energy up to 10%.…”
Section: Introductionmentioning
confidence: 99%